The Corporate Governance Effect on Financial Performance - Anggit Riyadi; Kartika Hendra Titisari; Purnama Siddi (Universitas Negeri Gorontalo, 2021)
This study aims to examine corporate governance effecton the financial performance of manufacturing companies in the food and beverage industry sector in the Indonesia Stock Exchange in 2014 - 2018. The independent variables in this study are the audit committee, the board of commissioners, the board of directors, and debt to equity ratio (DER). Whereas the dependent variable in this test is Return on Equity (ROE). The sampling technique is done by using purposive sampling method, namely the determination of sampling with certain considerations. Data analysis techniques include (1) Descriptive Statistics (2) Classical Assumption Tests covering Normality, Multicollinearity, Heteroscedasticity, and Autocorrelation (3) Multiple Linear Regression Tests (4) F Tests (5) Hypothesis Tests (6) Determinant Coefficient Test (R2) . The sample used in this test is manufacturing companies in the food and beverage industry sector which were listed on the Indonesia Stock Exchange in 2014 - 2018, with a total of 10 companies and there were 50 samples that met the criteria. The results of this test concluded that the variables of the board of directors and debt to equity ratio (DER) affect financial performance, while the variables of the audit committee and the board of commissioners have no effect on financial performance.